A better foundation for national security? The ethics of national risk assessments in the Nordic region - Lidén, Kristoffer (Cooperation and conflict, 2023)
Aiming at analysing all major security risks to a country, comprehensive National Risk Assessments (NRAs) can be used as a foundation for national security policies. Doing so manifests a modernist dream of securing societies through the anticipatory governance of risks. Yet, this dream resembles a nightmare of undemocratic state control in the name of security. Based on a critique of the politics of NRAs, this article offers a theoretical framework for evaluating their scientific and political credentials. Drawing on political theory of technocratic expert rule, ethical criteria of epistemic reliability and political representation are introduced to the debate. These criteria are then applied to an analysis of the NRAs of Sweden, Denmark, Finland, Norway and Iceland. I argue that although these NRAs are convincing correctives to the risk perceptions of politicians and civil society, they are insufficiently reliable and representative for defining the scope and priorities of national security policies at large.